The effect of Discrete Heaters on the rotating flow - BOUGHEZALA HAMAD Ahmed; BOUABDALLAH Said; BOUKHARI Ali (university Of Eloued جامعة الوادي, 2020)
The present numerical study investigates the laminar mixt convection heat in an enclosure with discrete heaters. Three different cases are considered based on the number of discrete heaters which is maintained at isothermal condition Th (Th > Tc). The right vertical wall is maintained at cold temperature Tc and the remaining all other walls are thermally insulated. The above schematic setup can be modeled into mathematical form and the governing non-dimensional equations are solved using Finite Volume Method. SIMPLE algorithm is employed for the pressure-velocity coupled momentum equations. Numerical simulations are carried out to find the effect of different Richardson Ri ranging from 0.1 to 10.0 and the distribution of discrete heaters. Results are given in the form of streamlines, isotherms, the velocity profiles and average Nusselt number. It is found that the maximum heat transfer rate is achieved for the distribution of discrete heater.
Intervention
Keywords: Discrete Heater; Mixt Convection; finite volumes; Richardson number